OCCUPATIONAL ROLE STRESS AND ORGANISATIONAL CYNICISM AMONG POLICE OFFICERS: THE ROLE OF RESILIENCE - Okonkwo, Kosisochukwu D.; Okonkwo, Ejike A.; Obodo, Paul I.; Okolo, Maxmillian C. (African Journal of Social and Behavioural Sciences, 2025)
On the basis of the assumption of organisational role theory, this correlational study investigated the moderating role of resilience in occupational role stress and organisational cynicism in a sample of police officers in Enugu Metropolis, Southeast Nigeria. Two hundred and sixty-four police officers comprising 200 males and 64 females between the ages of 26 and 55 years (M=44.07, SD=5.82) participated in the study. They were selected via a two-stage (cluster and purposive) sampling technique. The 13-item organisational cynicism scale, 60-item occupational role stress, and 6-item brief resilience scale were completed by the participants. The results of hierarchical multiple regression analysis revealed that only the role boundary component of occupational role stress positively predicted cognitive, affective, and behavioural dimensions of organisational cynicism, respectively. Resilience positively moderated the role ambiguity component of occupational role stress and the cognitive dimension of organisational cynicism. Based on these findings, this study recommends that the Nigeria police force and other relevant stakeholders should consider occupational role stress, especially role boundary and role ambiguity during recruitment, in order to minimize organisational cynicism among police officers. In addition, these bodies should also make policies to strengthen regular tactical training of these officers in order to enhance their resilience for effective policing, thus curtailing heightened insecurity in Nigeria.